Cajaninstilbene Acid Ameliorates Acetaminophen-Induced Liver Injury Through Enhancing Sestrin2/AMPK-Mediated Mitochondrial Quality Control - Yan, Mingzhu; Jin, Suwei; Liu, Yongguang; Wang, Lisha; Wang, Zhi; Xia, Tianji; Chang, Qi (Frontiers in Pharmacology, 2022)
Acetaminophen (APAP)-induced liver injury (AILI) is the main cause of acute liver failure in the developed countries. The present study aimed to evaluate the therapeutic efficacy of cajaninstilbene acid (CSA), a major stilbene compound derived from the leaves of pigeon pea [Cajanus cajan (L.) Millsp.], against AILI. CSA (50, 75 mg/kg, p. o.) was administered to male C57BL/6 N mice 0.5 h after a toxic dose of APAP (300 mg/kg, i. p.). The direct effect of CSA on hepatocytes was tested on primary mouse hepatocytes. Serum transaminases, hematoxylin and eosin staining, TUNEL and propidium iodide staining were used to assess hepatic damage and cell death. The results demonstrated that APAP-induced liver injury was ameliorated by CSA, as evidenced by decreased alanine aminotransferase and aspartate aminotransferase levels in the serum, and fewer necrotic and apoptotic hepatocytes in vitro and in vivo. Consequently, the inflammation in response to APAP overdose was inhibited by CSA. Without affecting APAP metabolic activation, CSA interrupted the sustained JNK-Sab-ROS activation loop and alleviated oxidative stress. Additionally, CSA promoted mitochondrial quality control, including mitochondrial biogenesis and mitophagy, as revealed by increased PGC-1α, TFAM, LC3-Ⅱ, PINK1 and mitochondrial Parkin expression and decreased p62 expression. Further mechanistic investigations showed that independent of CAMKK2, LKB1-mediated AMPK activation, which was promoted by Sestrin2, might be responsible for the protective effect of CSA. Our study demonstrates that CSA alleviates APAP-induced oxidative stress and enhanced mitochondrial quality control through Sestrin2/AMPK activation, thereby protecting against AILI,.